Delivering the News With Compassion: The GRIEV_ING Death Notification Protocol - Cherri Hobgood; Joey Woodyard; Susan Sawning; Katherine Savage (Association of American Medical Colleges, 2010)
Abstract Introduction Nearly 2.4 million deaths occur annually, over a million of which take place in hospitals. As a result, death notification remains a daunting and emotionally challenging task that physicians encounter throughout their careers. However, in one study, fewer than half of all physicians reported receiving death notification education in medical school or residency, while in another, 94% reported that such education is needed. Nevertheless, no validated educational interventions exist that are specifically designed to teach medical students, residents, and fellows effective skills in death notification that can be implemented in a practical time frame and allow easy integration into busy schedules. To address this need, a 2-hour-long educational intervention based on the GRIEV_ING Death Notification Protocol was developed and validated. The intervention provides a complete teaching and learning module composed of small-group, role-play, and didactic experiences to train residents and medical students in effective death notification skills. Methods This resource is a comprehensive teaching and learning module designed to provide educators with practical, proven teaching and assessment tools to help residents and medical students develop confidence and competence in death notification. The resource includes a PowerPoint presentation that provides training on the GRIEV_ING mnemonic, as well as documents that detail small-group activities in the form of structured discussions and role-plays to facilitate interactive learning. The resource also includes a self-efficacy survey, detailed standardized survivor scenarios, and assessment tools such as a Relationship and Communication Instrument and the GRIEV_ING Competence Instrument to help gauge progress. Results In one study, 20 residents significantly improved and retained their confidence and competence in death notification following exposure to this intervention. In another study, all 138 fourth-year medical students who were exposed to this intervention improved their overall competence and self-confidence in death notification. In addition, students who were exposed to a simulated survivor and provided feedback on their performance, in addition to being taught the GRIEV_ING protocol, improved their competence and confidence significantly. Discussion The significance of this resource is that it addresses an important educational need by providing practical, proven, and effective teaching and assessment tools to help students learn effective death notification skills.